Investigating dysbiosis and microbial treatment strategies in inflammatory bowel disease based on two modified Koch’s postulates - Zhao, HanZheng; Zhang, WenHui; Cheng, Die; You, LiuPing; Huang, YueNan; Lu, YanJie (Frontiers in Medicine, 2022)
Inflammatory bowel disease (IBD) is a chronic non-specific inflammatory disease that occurs in the intestinal tract. It is mainly divided into two subtypes, i.e., the Crohn's disease (CD) and ulcerative colitis (UC). At present, its pathogenesis has not been fully elucidated, but it has been generally believed that the environment, immune disorders, genetic susceptibility and intestinal microbes are the main factors for the disease pathogenesis. With the development of the sequencing technology, microbial factors have received more and more attention. The gut microbiota is in a state of precise balance with the host, in which the host immune system is tolerant to immunogenic antigens produced by gut commensal microbes. In IBD patients, changes in the balance between pathogenic microorganisms and commensal microbes lead to changes in the composition and diversity of gut microbes, and the balance between microorganisms and the host would be disrupted. This new state is defined as dysbiosis. It has been confirmed, in both clinical and experimental settings, that dysbiosis plays an important role in the occurrence and development of IBD, but the causal relationship between dysbiosis and inflammation has not been elucidated. On the other hand, as a classic research method for pathogen identification, the Koch's postulates sets the standard for verifying the role of pathogens in disease. With the further acknowledgement of the disease pathogenesis, it is realized that the traditional Koch's postulates is not applicable to the etiology research (determination) of infectious diseases. Thus, many researchers have carried out more comprehensive and complex elaboration of Koch's postulates to help people better understand and explain disease pathogenesis through the improved Koch's postulates. Therefore, focusing on the new perspective of the improved Koch's postulates is of great significance for deeply understanding the relationship between dysbiosis and IBD. This article has reviewed the studies on dysbiosis in IBD, the use of microbial agents in the treatment of IBD, and their relationship to the modified Koch’s postulates.